Homo Deus: A Brief History of Tomorrow - Harari, Yuval Noah (London Vintage, 2017)
Yuval Noah Harari envisions a near future in which we face a new set of challenges. Homo Deus explores the projects, dreams and nightmares that will shape the twenty-first century and beyond - from overcoming death to creating artificial life. It asks the fundamental questions: how can we protect this fragile world from our own destructive power? And what does our future hold?
Keywords: Sociological Theories; Anthropology & Sociology Biographies; Bioengineering